Dosimetric evaluation of scattered and attenuated radiation due to dental restorations in head and neck radiotherapy. Issue 1 (January 2018) - Azizi, Mona; Mowlavi, Ali Asghar; Ghorbani, Mahdi; Azadegan, Behnam; Akbari, Fatemeh
Abstract: In radiotherapy of head and neck cancer, the presence of high density materials modifies photon dose distribution near these high density materials during treatment. The aim of this study is to calculate the backscatter and attenuation effects of a healthy tooth, Amalgam, Ni-Cr alloy and Ceramco on the normal tissues before and after these materials irradiated by 6 and 15 MV photon beams, respectively. All measurements were carried out in a water phantom with dimension of 50 × 50 × 50 cm 3 with an ionization chamber detector. Two points before and four points after the dental sample were considered to score the photon dose. The depth dose on the central beam axis was explored in a water phantom for source to surface distance (SSD) of 100 cm in a 10 × 10 cm 2 field size. The percentage dose change was obtained relative to the dose in water versus depth of water, tooth, Amalgam, Ni-Cr alloy and Ceramco for the photon beams. The absolute dose (cGy) was measured by prescription of 100 cGy dose in the water phantom at depth of 2.0 and 3.1 cm for 6 and 15 MV photons, respectively. At depth of 0.6 cm, the maximum percentage dose increase was observed with values of 6.99% and 9.43%for Ni-Cr and lowest percentage dose increase of 1.49% and 2.63% are related to the healthy tooth in 6 and 15 MV photon beams, respectively. The maximum absolute dose of 95.58 cGy and 93.64 cGy were observed at depth of 0.6 cm in presence of Ni-Cr alloy for 6 and 15 MV photon beams, respectively. The presence of dental restorations can cause backscattering dose during head and neck radiation therapy. Introduction of compositions and electron density of high density materials can improve the accuracy of dosimetric calculations in treatment planning systems to deliver the relevant dose to target organ and reduce the backscattering dose in healthy tissues in the surrounding of tooth.